2022
DOI: 10.1001/jamanetworkopen.2022.20680
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mild Cognitive Impairment or Probable Dementia in New Users of Angiotensin II Receptor Blockers and Angiotensin-Converting Enzyme Inhibitors

Abstract: Key Points Question Is initiation of angiotensin II receptor blockers (ARBs), compared with angiotensin-converting enzyme inhibitors (ACEIs), associated with a reduced risk of cognitive impairment, after controlling for potential pretreatment confounders? Findings This active-comparator, new-user design cohort study identified 2040 new users of ACEIs/ARBs from the Systolic Blood Pressure Intervention Trial (SPRINT). The overall risk of cognitive impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(95 reference statements)
1
0
0
Order By: Relevance
“…Our findings on the contrasting risk of AD and ADRD between angiotensin-II stimulating vs. inhibiting antihypertensive drugs in a large cohort of men and women with colorectal cancer support the results and conclusions of previous studies by van Dalen et al (10), Marcum et al (11), and other researchers (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Although each study population was different, the magnitude and direction of the risk of AD and ADRD associated with angiotensin-II stimulating or inhibiting antihypertensive medications were consistent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on the contrasting risk of AD and ADRD between angiotensin-II stimulating vs. inhibiting antihypertensive drugs in a large cohort of men and women with colorectal cancer support the results and conclusions of previous studies by van Dalen et al (10), Marcum et al (11), and other researchers (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Although each study population was different, the magnitude and direction of the risk of AD and ADRD associated with angiotensin-II stimulating or inhibiting antihypertensive medications were consistent.…”
Section: Discussionsupporting
confidence: 91%
“…Marcum and colleagues (11) did a secondary analysis of participants aged ≥50 years with hypertension in the randomized Systolic Blood Pressure Intervention Trial (SPRINT) in 2011-2018 with a median of 4.8 years of follow-up, and also found that the risk of amnestic mild cognitive impairment (MCI) was significantly lower (hazard ratio: 0.74; 95% CI: 0.64-0.87) and probable dementia was insignificantly lower (0.80; 0.57-1.14) in those receiving stimulating-only vs. those inhibiting-only users. These associations between angiotensin-II stimulating antihypertensive users and a lower risk of ADRD were also reported in other studies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionsupporting
confidence: 85%
“… 38 These observations could represent important subpopulations that may particularly benefit from ARB versus ACEI initiation to prevent adverse CVD endpoints and merit further investigation. Similar to our prior report comparing the risk of cognitive outcomes among ARB versus ACEI new users, 39 the current analysis reports a lower adjusted risk of CVD among new users of an ARB versus ACEI in the standard treatment arm, but not the intensive SBP treatment arm. As with all subgroup analyses, these results should be interpreted with caution and indicate that the specific renin‐angiotensin system inhibitor (ARB or ACEI) may not meaningfully impact CVD events because of the substantial, independent benefit of intensive BP lowering.…”
Section: Discussionsupporting
confidence: 85%
“…Freeman et al, (2020) Drug-resistant epilepsy, early-onset hypertension and white matter lesions: a hidden paraganglioma Silvennoinen et al, (2019) Effect of Intensive Blood Pressure Control on Carotid Morphology and Hemodynamics in Chinese Patients with Hyperhomocysteinemia-Type Hypertension and High Risk of Stroke Wu et al, (2019) Effect of intensive blood pressure control on subtypes of mild cognitive impairment and risk of progression from SPRINT study Gaussoin et al, (2022) Emergência hipertensiva e acidente vascular cerebral isquêmico e hemorrágico: conceitos atuais de tratamento Giannini et al, (2014) Equimolar doses of hypertonic agents (saline or mannitol) in the treatment of intracranial hypertension after severe traumatic brain injury Huang et al, 2020 Etiology, classification, and epidemiology of stroke Caplan, LR et al, (2016) Fatal intracranial haemorrhage in a hypertensive patient with atrial fibrillation and coronavirus disease 2019 ZONNEVELD et al, 2018). Como também, o uso do IECA e BRA contribuiu para redução do risco de resultados cognitivos ruins, demonstraram melhorar a memória episódica e as habilidades visuoespaciais (COHEN et al, 2022).…”
Section: Justificativamentioning
confidence: 99%